IDENTIFIKASI MORFOLOGI DAN ANATOMI JERUK LOKAL (Citrus sp.) DI DESA HANGIRA DAN DESA BALEURA KECAMATAN LORE TENGAHKABUPATEN POSO - Rezkianti, Vivin; Maemunah, Maemunah; Lakani, Irwan (AGROTEKBIS, 2016)
The research aiming at identifying morphology and anatomy of (Citrus sp.) at Hangira Village and Baleura Village of Central Lore Sub-District of Poso Regency was conducted in September until November 2015 and the observation of anatomy was held at Pest and Plant Disease Laboratory of Faculty of Agriculture of Tadulako University. The researcher used descriptive method with direct survey in location of research. The determination of the location was based on the information and survey having been done at Hangira Village and Baleura Village of Central Lore Sub-District of Poso Regency. The observation was done based on morphological character of form and colourof the stem, form of branching, canopy, canopyâs diameter, stemâs surface, edge and tip of the leaves, leaf symetry, flush colour, upper and lower surfaces of leaves, flesh of leaf, leaf size, colour of leaf stalk, form of stalk, and length of stalk. The anatomical character of the leaf consists of stomatal density and index. The analysis was then continued by using cluster analysis of SYSTAT 8.0software program.Â Key Words: Anatomy, Citrus, morphological character.